PENGENDALIAN PENCEMARAN AIR UNTUK KESEHATAN LINGKUNGAN YANG LEBIH BAIK DI KABUPATEN SUMENEP - Drajat, M. Raofikin; Fithry, Abshoril (2024)
The progress in the industrial sector has the potential to produce waste that can pollute and damage the environment. Wastewater is a major problem because it can have a negative impact on the environment and public health. Water pollution occurs because business owners does not manage wastewater at Wastewater Treatment Plant (IPAL). This research aims to analyze the implementation of water pollution control policy especially that caused by the shrimp pond industry in Sumenep Regency and solving the problems. This research is a normative juridical research, legal science approach and primary data as the main data is obtained from various legal materials related to research supported also by secondary and tertiary data as additional data. The results showed that the implementation of Sumenep Regency Regent Regulation No. 1 of 2016 concerning Water Quality Management and Water Pollution Control has not been implemented properly. It is necessary to create policies to control industrial wastewater pollution by the preparation of Regional Regulations, which contain criminal and/or administrative sanctions, and also contain the obligation for every shrimp pond owner must be equipped with IPAL so it’s more effective to protecting the environment and disciplining the society.